2017
DOI: 10.1039/c6ra26868d
|View full text |Cite
|
Sign up to set email alerts
|

Achieving electroreduction of CO2to CH3OH with high selectivity using a pyrite–nickel sulfide nanocomposite

Abstract: An FeS2/NiS electrocatalyst could selectively reduce CO2to CH3OH with an unprecedented overpotential of 280 mV and high faradaic efficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(30 citation statements)
references
References 40 publications
1
29
0
Order By: Relevance
“…While at –1.2 V vs. NHE in KHCO 3 HER is still the dominating reaction, the contribution of the CO 2 RR is slightly improved revealing faradaic efficiencies of 1.2% (CO), 1.8% (CH 4 ), 0.3% (C 2 H 6 ) and 61.5% (H 2 ). The observed performance of Fe 4.5 Ni 4.5 S 8 is in good agreement with the reports on greigite and pyrite in aqueous conditions 13,14,35…”
Section: Resultssupporting
confidence: 91%
“…While at –1.2 V vs. NHE in KHCO 3 HER is still the dominating reaction, the contribution of the CO 2 RR is slightly improved revealing faradaic efficiencies of 1.2% (CO), 1.8% (CH 4 ), 0.3% (C 2 H 6 ) and 61.5% (H 2 ). The observed performance of Fe 4.5 Ni 4.5 S 8 is in good agreement with the reports on greigite and pyrite in aqueous conditions 13,14,35…”
Section: Resultssupporting
confidence: 91%
“…Protonation of adsorbed *CO 2 − into *HCOO − takes place that gets desorbed with ease due to low affinity for chemisorption with carbon supports, thus generating HCOOH with high selectivity. In another study, the fabrication of low costing, highly efficient heterostructured electrocatalyst using earth abundant transition metals, FeS 2 /NiS nanocomposites (average diameter size distribution of about 14 nm), for the reduction of CO 2 to CH 3 OH was demonstrated by Zhao et al [76] The as‐developed catalyst demonstrated high FE of up to 64% over low overpotentials of 280 mV at –0.6 V versus RHE. Compositing of FeS 2 with NiS gives rise to earlier reduction onset potentials while also enhanced current densities reaching 7.8 mA cm −2 at –0.68 V (Figure 6B, third image).…”
Section: Heterostructures In Electrocatalytic Co2 Reductionmentioning
confidence: 99%
“…Electrochemical reduction of CO 2 to methanol (CH 3 OH) catalysed by transition metals has been proved feasible and effective in aqueous electrolytes. Zhao et al . demonstrated that FeS 2 /NiS nanocomposite can catalyse CO 2 RR at an unprecedented over‐potential of 280 mV and a high CH 3 OH faradaic efficiency up to 64% at the potential of ∼ 0.6 V. The FeS 2 /NiS catalyst performed a stable current density of 3.1 mA cm −2 over the 4 hours stability test.…”
Section: Introductionmentioning
confidence: 99%